Responses of maize hybrids developed for drought tolerance to low soil nitrogen - Meseka, S.K.; Menkir, A.; Elhassan, A.; Ibrahim, S.S.; Ajala, S.; Kamara, A. (2006)
High cost of nitrogen fertilizer coupled with frequent occurrence of drought has forced many maize (Zea mays L.) growers in sub-Saharan Africa to either apply fertilizer below optimal dose or no fertilizer to their maize fields. The objectives of this study were to (i) compare the performance of four hybrid groups developed for drought tolerance under low nitrogen and (ii) identify some adaptive secondary traits that contribute to yield improvement. Ninety-six hybrids along with four checks, arranged in a 10 x 10 triple lattice design, were evaluated under both low and high N at Mokwa, Nigeria, in the rainy season in 2002 and 2003. Genotype x nitrogen interaction was highly significant (P 0.01) for all traits, except the second leaf death score. On the average, hybrids of tolerant x tolerant (T x T), tolerant x susceptible (T x S) and S x T crosses had higher grain yields compared to S x S crosses under N. No marked differences in grain yields and other agronomic traits were obtained among hybrid groups under high N. Both simple correlation and principal component analyses were effective statistical tools in determining adaptive secondary traits that contributed to grain yield. Yield improvement was associated with increased number of ears plantE-1, prolonged stay-green, low ear placement short plants and anthesis-¬silking interval. The top best hybrids were 01A11958B, 01A11988B, 01A12084B, 01A12096B, 01A11972B and Oba Super1 (check).